HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN MOTIVASI BELAJAR MAHASISWA - I Gede Ardi Suyasa (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Family is something that can not be separated from someone, family being the most important driving force in everything. Family support is one of the factors that affect student motivation to learn that is used to achieve the objectives. The results of preliminary studies was found that a variety of reasons students become nursing department student for purely selfish desires and also for not getting what they want major, went along with friends and others. The purpose of this study was to determine the relationship between family support of student learning motivation at PSIK FK UNUD. The design of this study was a cross-sectional design. Respondents in this study were 180 respondents at PSIK FK UNUD on May 2014 were selected by simple random sampling, analysis using the Spearman Rank correlation test. Students PSIK FK unud most have good family support that 125 people (69.4%) and most have a high motivation to learn that 167 people (92.8%). The result was significant relationship between family support of student learning motivation at PSIK FK UNUD (? <0.05). Provide good family support for students to increase their learning motivation which is used to achieve the purpose that want to be achieved with the result that students feel cared for and comfortable.